The Influence of Immunization and Population Density to Diphtheria’s Prevalence in East Java - Dwi Elsa Mardiana (Jurnal Berkala Epidemiologi, 2018)
ABSTRACTBackground: The south-east Asia region had contributed the highest cases of diphtheria in the worldwide, and Indonesia had the second highest insidence of diphtheria in the worldwide after India. In East Java, there were 348 diphtheria cases had been reported with case fatality rate (CFR) of 1.72. Purpose: This study aimed to analyze the influence of immunization and population density on the prevalence of diphtheria in East Java Province in 2016. Methods: The design of this observational study was cross-sectional. The population of this study was all patients diagnosed with diphtheria from 29 districts in 9 cities of East Java. Data were obtained from the health profile of East Java in 2016. The independent variables were complete primary immunization and population density, while the dependent variable was the prevalence of diphtheria. Data were analyzed through multiple linear regression. Results: The prevalence of diphtheria in East Java was low or 8.91 per 1000,000 in 2016. Two factors determined the prevalence of diphtheria, namely complete primary immunization and population density (p=0.01). Conclusion: Both complete primary immunization and population density had a significant influence on the prevalence of diphtheria.Keywords: diphtheria; immunization; east java; population density